(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Due to its reduced invasiveness, low rejection rate, and remarkable ease of administration, transdermal drug delivery (TDD) has recently become a viable alternative to oral and injectable administration. The transdermal medication delivery method is a treatment strategy that is extraordinarily safe and well-tolerated and has enormous potential for delivering active ingredients against a variety of illnesses. However, because to the low skin permeability of the majority of active medicines in the formulation, its application is currently restricted in clinical settings. To get over this restriction, new strategies for skin permeation improvement techniques are offered. The drug delivery industry has undergone a revolution due to recent advances at the nano and microscale. A growing trend in drug delivery applications is the use of several kinds of microneedles (MNs), in particular because they are safe, compliant with patient preferences, and practical. Microneedles are a distinct, cutting-edge, and successful method created to administer medicinal chemicals and immunological components in a number of disorders. With appropriate examples and recent developments, various MN types—solid, hollow, coated, dissolving, and hydrogel forming—are described. We summarize recent developments in microneedles for therapeutic uses in this review.